The Antitumor Activity of Combinations of Cytotoxic Chemotherapy and Immune Checkpoint Inhibitors Is Model-Dependent - Grasselly, Chloé; Denis, Morgane; Bourguignon, Aurore; Talhi, Nolan; Mathe, Doriane; Tourette, Anne; Serre, Laurent; Jordheim, Lars Petter; Matera, Eva Laure; Dumontet, Charles (Frontiers in Immunology, 2018)
In spite of impressive response rates in multiple cancer types, immune checkpoint inhibitors (ICIs) are active in only a minority of patients. Alternative strategies currently aim to combine immunotherapies with conventional agents such as cytotoxic chemotherapies. Here, we performed a study of PD-1 or PDL-1 blockade in combination with reference chemotherapies in four fully immunocompetent mouse models of cancer. We analyzed both the in vivo antitumor response, and the tumor immune infiltrate four days after the first treatment. In vivo tumor growth experiments revealed variable responsiveness to ICIs between models. We observed enhanced antitumor effects of the combination of immunotherapy with chemotherapy in the MC38 colon and MB49 bladder models, a lack of response in the 4T1 breast model, and an inhibition of ICIs activity in the MBT-2 bladder model. Flow cytometry analysis of tumor samples showed significant differences in all models between untreated and treated mice. At baseline, all the tumor models studied were predominantly infiltrated with cells harboring an immunosuppressive phenotype. Early alterations of the tumor immune infiltrate after treatment were found to be highly variable. We found that the balance between effector cells and immunosuppressive cells in the tumor microenvironment could be altered with some treatment combinations, but this effect was not always correlated with an impact on in vivo tumor growth. These results show that the combination of cytotoxic chemotherapy with ICIs may result in enhanced, similar or reduced antitumor activity, in a model- and regimen-dependent fashion. The present investigations should help to select appropriate combination regimens for ICIs.